DILEMATIKA PENANGANAN PENGUNGSI ROHINGNYA DI PROVINSI ACEH DAN DAMPAKNYA TERHADAP CITRA NEGARA INDONESIA - Novialdi, Risky (Global and Policy Journal of International Relations, 2026)
The humanitarian crisis affecting the Rohingya people is no longer a hidden reality. Mass atrocities against the Rohingya ethnic group have been occurring for many years. Reports of ethnic cleansing carried out by the Myanmar government against the Rohingya have spread globally through both mass media and social media platforms. This prolonged humanitarian crisis has forced the Rohingya to flee their homeland, with Indonesia becoming one of the countries where they seek refuge and safety. However, a critical question arises: are the Rohingya refugees purely fleeing humanitarian persecution, or are there other underlying interests that influence their arrival in Indonesia? This study employs a qualitative research method, emphasizing explanatory data derived from in-depth interviews and document analysis involving various stakeholders related to the handling of Rohingya refugees in Aceh Province. The findings reveal numerous irregularities in the management of Rohingya refugees. These include cases of refugees escaping from temporary shelters and a gradual decrease in the number of refugees over time. Furthermore, the handling of Rohingya refugees indicates the involvement of certain actors who allegedly exploit the Rohingya humanitarian crisis as an opportunity for personal or economic gain. In conclusion, this study finds that significant improvements are still required from the Indonesian government, particularly in Aceh Province, regarding the management of Rohingya refugees. Inadequate handling not only exacerbates humanitarian vulnerabilities but may also negatively affect Indonesia’s international image in the global arena.